Distinct strategies to overcome severe forms of PKU: The p.G46S as a model to identify small molecules modulators of protein aggregation and evaluation of an enzyme replacement approach using a nanoparticulate system - Costa, Ana Carolina Ramos (2017)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2017